Mongolia’s Strategic Choice - the OSCE - Sukhbaatar, Chandmani (Mongolian Journal of Strategic Studies, 2025)
Mongolia’s accession to the Organization for Security and Cooperation in Europe (OSCE) in 2012 marked a historic milestone in its foreign policy and international identity. As the first Northeast Asian state to join, Mongolia demonstrated its ambition to extend engagement beyond its immediate neighbors and integrate into the EuroAtlantic community. Rooted in the democratic transition of the early 1990s, this decision reflected Mongolia’s independent foreign policy and its “Third Neighbor Policy,” aimed at diversifying partnerships with likeminded democracies and multilateral organizations. Pragmatically, OSCE membership provided platforms for security cooperation, border management, election monitoring, and capacity building. Strategically, it reinforced Mongolia’s sovereignty, democratic values, and visibility as an “Oasis of Democracy.” The pathway to membership involved years of partnership as an Asian Partner for Cooperation, culminating in full participation despite geographic debates. Since accession, Mongolia has actively contributed to OSCE initiatives, hosting major forums, welcoming election observers, and promoting gender equality in peacekeeping. Its neutrality and geographic position have enabled Mongolia to act as a mediator, exemplified by the Ulaanbaatar Dialogue. Looking ahead, Mongolia seeks to deepen cooperation in democracy, sustainable development, and regional security dialogue, positioning itself as a bridge between Europe and Asia. Монгол Улсын стратегийн сонголт – ЕАБХАБ Хураангуй Монгол Улс 2012 онд Европын аюулгүй байдал, хамтын ажиллагааны байгууллага (ЕАБХАБ)-д элссэн нь гадаад бодлого болон олон улсын нэр хүндийн хувьд түүхэн үйл явдал болсон юм. 1990-ээд оны ардчилсан шилжилтээс эхтэй энэ шийдвэр нь Монголын бие даасан гадаад бодлого болон “Гуравдагч хөршийн бодлого”-ыг илэрхийлж, ардчиллын үнэт зүйлсээр холбогддог орнууд болон олон улсын байгууллагуудтай харилцаагаа төрөлжүүлэх зорилготой байв. Практик талаасаа ЕАБХАБ-ын гишүүнчлэл нь аюулгүй байдлын хамтын ажиллагаа, хил хамгаалалт, сонгуулийн ажиглалт, чадавх бэхжүүлэх шинэ талбаруудыг Монголд олгосон. Стратегийн хувьд энэ нь Монголын тусгаар тогтнол, ардчилсан үнэт зүйлсийг бататгаж, “Ардчиллын баянбүрд” хэмээх нэр хүндийг улам бэхжүүлж чадсан. Тус байгууллагын гишүүн болсноор Монгол Улс ЕАБХАБ-ын санаачлагад идэвхтэй оролцож, томоохон чуулга, уулзалтууд зохион байгуулж, сонгуулийн ажиглагчдыг урьж, энхийг сахиулах ажиллагаанд эмэгтэйчүүдийн оролцоог нэмэгдүүлэх зэрэг бодит хувь нэмэр оруулж ирсэн. Геополитикийн төвийг сахисан байр суурь нь Монголыг зуучлагчийн хувьд итгэлтэй түнш болгож байгаа бөгөөд Улаанбаатарын яриа хэлэлцээ санаачлагчаар улам бататгаж байгаа юм. Цаашид Монгол Улс ардчилал, тогтвортой хөгжил, бүс нутгийн аюулгүй байдлын яриа хэлэлцээг гүнзгийрүүлэх зорилготой бөгөөд Европ, Азийг холбосон гүүр болох байр сууриа бататгахыг эрмэлзэж байна. Түлхүүр үг: ЕАБХАБ-ын гишүүнчлэл, Гуравдагч хөршийн бодлого, Монгол Улсын гадаад бодлого, ардчилал